Negative rumours about a vaginal ring for HIV-1 prevention in sub-Saharan Africa. Issue 11 (2nd November 2019) - Chitukuta, Miria; Duby, Zoe; Katz, Ariana; Nakyanzi, Teopista; Reddy, Krishnaveni; Palanee-Phillips, Thesla; Tembo, Tchangani; Etima, Juliane; Musara, Petina; Mgodi, Nyaradzo M.; van der Straten, Ariane; ,
Abstract: Rumours may influence health-related behaviours, including the uptake of and adherence to HIV prevention products. This study assessed the safety and effectiveness of a vaginal ring delivering the antiretroviral dapivirine for HIV prevention in Africa. We explored negative rumours about study participation and the vaginal ring amongst study participants and their communities in Malawi, Uganda, South Africa and Zimbabwe. In total 214 women participated in either single or serial in-depth interviews, or a focus group discussion. Three key findings emerged in the data. Firstly, rumours reflected fears concerning the ring and trial participation. Given the historical-political context of the countries in which the trial was conducted, the ring's investigational nature and its foreign origin, ring use was rumoured to cause negative health outcomes such as cancer and infertility and to be associated with practices such as witchcraft or Satanism. The salience of these rumours varied by country. Secondly, rumours reportedly affected participants' adherence to the ring, and other women's willingness to participate in the study. Finally, participants reported that participant engagement activities helped address rumours, resulting in enhanced trust and rapport between staff and participants.